2014
DOI: 10.4028/www.scientific.net/amr.938.170
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials in PU Foam for Enhanced Sound Absorption at Low Frequency Region

Abstract: Lot of research is going on to develop materials suitable for absorbing sound and reducing noise. By virtue of their superior vibration damping capability and attractive characteristics such as visco elasticity, simple processing and commercial availability, polyurethane foams are extensively applied not only in automotive seats but also in various acoustical parts. However, the sound absorption coefficient of polyurethane foams is high (0.8 1.0) in high frequencies in the range 300 to 10000Hz while it is foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…This study showed that in the case of simultaneous use of nano clay, PAN NF and PVDF NF, when nano clay and PVDF NF were the maximum and PAN NF was minimum, and also when PAN NF was the highest and PVDF NF and nano clay were the lowest, Young's modulus increased. One of the reasons for the growth of Young's modulus can be creation of effective nuclear sites between fillers and the foam structure [33]. Table 1 present the ANOVA results of for Response Surface Reduced Quadratic Model.…”
Section: Determination Of Morphologymentioning
confidence: 99%
“…This study showed that in the case of simultaneous use of nano clay, PAN NF and PVDF NF, when nano clay and PVDF NF were the maximum and PAN NF was minimum, and also when PAN NF was the highest and PVDF NF and nano clay were the lowest, Young's modulus increased. One of the reasons for the growth of Young's modulus can be creation of effective nuclear sites between fillers and the foam structure [33]. Table 1 present the ANOVA results of for Response Surface Reduced Quadratic Model.…”
Section: Determination Of Morphologymentioning
confidence: 99%
“…Kurangnya serat yang ditambahkan akan menurunkan kemampuan komposit untuk menahan beban yang diberikan, sehingga dapat dilihat dari pengujian, spesimen komposit yang seratnya lebih sedikit lebih getas [9]. Berdasarkan gambar 3 diatas dapat disimpulkan bahwa semakin banyak penambahan serat ke dalam komposit maka akan semakin meningkatkan nilai kekuatan lentur terhadap beban yang diterima oleh material komposit.…”
Section: Pendahuluanunclassified
“…Hence PU foams (flexible polyurethane) exhibiting high porosity have gained increasing use towards controlling noise. They have gained use in industrial scenarios because of their promising features or properties such as acoustic absorption properties, excellent viscoelasticity, being light in weight, and effective sound absorption [7,8]. However, most of polyurethane (PU) foams are based of raw materials from petroleum.…”
Section: Introductionmentioning
confidence: 99%